Endotoxin induces interleukin-1beta and nitric oxide synthase mRNA in rat hypothalamus and pituitary. - Satta, M; Jacobs, R; Kaltsas, G; Grossman, AB (1998)
The gases nitric oxide (NO) and carbon monoxide (CO) may be involved in hypothalamo-pituitary-adrenal axis (HPA) modulation. In the brain, NO is synthesized by two forms of NO synthase (NOS), a constitutive neuronal form (nNOS) and an inducible form (iNOS). There are also a constitutive heme oxygenase (HO2) and an inducible form (HO1) which generate CO. We have therefore investigated the effect of peripheral lipopolysaccharide (LPS) administration on the gene expression of these enzymes along with interleukin-1beta (IL-1beta) gene expression in the hypothalamus, pituitary and liver. Male Wistar rats (200-250 g body weight) were injected intraperitoneally with endotoxin (Escherichia coli, 055 B5) dissolved in sterile normal saline [250 microg/kg first group, 2.5 mg/kg (second group) and 6.25 mg/kg (third group)] in a final volume of 0.5 ml, or saline alone in the control group. The first and the second groups were studied 1, 3, 8 and 24 h after LPS (n = 4 per group); the third group was studied at 3 h. Total RNA was extracted from the hypothalamus, pituitary and liver, and cDNA was made using standard reverse transcriptase methods. Duplex polymerase chain reaction (PCR) was standardised in order to quantify the expression of a specific gene in relation to the 'house-keeping' gene beta-actin. The specific genes studied were iNOS, nNOS, HO1, HO2 and IL-1beta. The PCR products were separated on agarose gel and densitometric analysis of the bands allowed semi-quantification. In the second group, iNOS and IL-1beta were induced in hypothalamus, pituitary and liver, showing a peak at 3 h (p < 0.001), returning to baseline levels at 24 h. Neuronal NOS was not expressed in the liver under basal conditions or after LPS; in the hypothalamus and pituitary, nNOS was expressed basally but there was no change after LPS. In the first group, iNOS and IL-1beta were again induced in all three tissues studied, but with a delayed time course compared to the second and third groups; the peak change for IL-1beta occurred at 8 h (p < 0.05), again returning to baseline levels at 24 h. The peak for iNOS occurred at 24 h. HO1 and HO2 were expressed in all three tissues under basal conditions; HO1 was increased at 1 h in the liver in the second group, and at 3 h in the pituitary in the third group. There was no change in either HO1 or HO2 in the hypothalamus at any dose at any time point. We conclude that IL-1beta and iNOS are induced in rat hypothalamus and pituitary following various doses of endotoxin. We speculate that while IL-1beta may mediate stimulation of the HPA by endotoxin, NO generation may be involved in the counter-regulation of this response.